Parasotoid communities and genetic structure: host plant does not matter - Jourdie, Violaine (My University, 2008)
Plant-insect interactions have long been studied and reveal intricate mechanisms. Plants are capable of defending themselves both directly by poisoning insect herbivores and indirectly by emitting volatile compounds that are used by the natural enemies to localize their host. In response, insects have evolved strategies to defeat plant defense mechanisms. Because insect pests are affected by plant signals, their natural enemies also bear these effects. As host plant can affect the physiology and behavior of parasitoids, it may also contribute to shaping their population genetic structure. This thesis mainly aimed to investigate the effects of host plant on the population genetics of parasitoids of the fall armyworm (FAW), Spodoptera frugiperda J. E. Smith (Lepidoptera: Noctuidae), using microsatellite markers. The FAW is one of the New World’s most devastating pests and it attacks several economically important crops as well as grasses. It is commonly controlled by chemical insecticides. However, as it is attacked by numerous parasitoids species, and in order to limit the use of toxic pesticides, biological control is a safer alternative mean of management for this pest. The success of biological control relies on a good knowledge of the system, hence the importance of investigating population genetics and communities structure. This study focused on two primary parasitoids of S. frugiperda, Chelonus insularis Cresson (Hymenotera: Braconidae) and Campoletis sonorensis Cameron (Hymenoptera: Ichneumonidae). It was conducted on two host plants, maize and sorghum, in Mexico where maize originated and where sorghum was introduced barely over a century ago. Due to difficulties encountered during sampling, whereby immature parasitoids did not complete their life cycle and therefore could not be morphologically identified, a technique was first developed, as a cheaper and faster alternative to sequencing, to molecularly assign parasitoid larvae to species. This simple but nonetheless efficient technique consists in amplifying DNA through polymerase chain reaction and digesting it with a cocktail of restriction endonucleases in order to obtain a species specific pattern when the digestion product is run on an agarose gel. With this technique, we could get an accurate estimation of which species were collected and in what proportions, which allowed to study parasitoid community structure. The study of population genetics first required the development and optimization of reliable molecular markers. Fifteen and 13 highly polymorphic microsatellites were respectively isolated from C. sonorensis and from C. insularis. These markers were used to investigate fine-scale genetic structure in Mexican populations. We could discern a regional effect, but host plant seems to play no role in shaping the populations genetic structure. High levels of admixture indicate that gene flow between populations is considerable. Finally, genetic structure was investigated at larger scale through a phylogeography using sequences of mitochondrial and nuclear marker genes. The lack of local structure was confirmed for both species. We found however evidence for North-South migration through a single colonization event in C. insularis, and a cryptic species distributed in Canada was discovered. Dispersal of these insects seems to be largely driven by wind as suggested by genetic similarities between geographically very distant individuals.
Thèse de doctorat : Université de Neuchâtel, 2008 ; Th. 2050
Keywords: parasitoïde; Hymenoptera; Braconidae; Ichneumonidae; génétique des populations; structurations des communautés; Spodoptera frugiperda; légionnaire d’automne; Chelonus insularis; Campoletis sonorensis; plante-hôte; maïs; sorgho; microsatellites; phylogéographie; parasitoid; Hymenoptera; Braconidae; Ichneumonidae; population genetics; community structure; genetic structure; Spodoptera frugiperda; fall armyworm; Chelonus insularis; Campoletis sonorensis; host plant; maize; sorghum; microsatellites; phylogeography